Concepts to Maximize the Usage of Distribution Networks - Case study on Jaffna Peninsula Distribution System - Ravindran, N.; Rodrigo, W.D.A.S.; Prasad, W.D.; Atputharajah, A. (My University, 2018)
Usage of distribution networks are always a challenging task as it directly connected to the consumer loads, which are continuously varying. Under or over voltages are one of the major component that limits the expansion of electrical distribution system. This can be eliminated by operating all devices to their optimize positions. This done through applied research study in this paper, which resulted a concept on operational steps while giving a cost effective solution in overall. Here the PSCAD Bergeron model is used for modelling the Jaffna peninsula electrical distribution system. The operation is studied for the full day load pattern thus showed voltage problems in some bus bars especially during peak load conditions. Solutions are proposed and healthy operation is validated with proposed solution. Further the concept on finding the solution is also concluded a general contribution from this study.
Keywords: Distribution system study; under voltage